Islamic marketing: promotional campaign in the perspective of Maqasid As-Shariah in Malaysia / Mohammad Firdaus Mohamad ... [et al.] - Mohamad, Mohammad Firdaus; Mohammed, Rozita @ Uji; Mawardi, Faiqah; Abdullah, Hasimi (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2019)
The concept of marketing in business refers to product, price, place and promotions (4p's). In the era of globalization and technology, the application of Islamic marketing principles in promotional campaign is beginning to be discussed by scholars who seek for the suits that areAs-Shariah compliant. The current global market for Islamic products and services is valued of more than USD 2.3 trillion a year. Halal food products represent 60% of the market value with the total of USD 680 trillion worldwide. This attracts many researchers to develop an Islamic marketing concept that is compliant to the Shariah law and the way of religion (ad- deen). Malaysia has a population of more than 30 million, with about 60% of this are Muslims. This research can help marketers to create appropriate content in marketing a product or service that is compliant to Islamic principles. The approach of using promotional campaign which is aligned with the concept of Maqasid As-Shariah needs to be highlighted not only to gain profit but also to serve here after obligations. This research aims to improvise the ways promotional campaign are being done from the perspective of Maqasid As-Shariah in catering the Muslims market in Malaysia.